2010
DOI: 10.1002/nbm.1587
|View full text |Cite
|
Sign up to set email alerts
|

Measuring perfusion and bioenergetics simultaneously in mouse skeletal muscle: a multiparametric functional‐NMR approach

Abstract: A totally noninvasive set-up was developed for comprehensive NMR evaluation of mouse skeletal muscle function in vivo. Dynamic pulsed arterial spin labeling-NMRI perfusion and blood oxygenation level-dependent (BOLD) signal measurements were interleaved with (31)P NMRS to measure both vascular response and oxidative capacities during stimulated exercise and subsequent recovery. Force output was recorded with a dedicated ergometer. Twelve exercise bouts were performed. The perfusion, BOLD signal, pH and force-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 44 publications
3
22
0
2
Order By: Relevance
“…Over the last decade, analysis of PCr recovery kinetics has been extensively used in order to investigate in vivo skeletal muscle mitochondrial oxidative capacity [41], [42]. Previous animal studies reported PCr recovery times typically ranging from ∼50 sec to ∼160 sec according to the end-of-exercise pH values [31], [41], [43]. From a methodological point of view, it should be pointed out that PCr recovery is usually fitted with a monoexponential function so that the temporal resolution of the raw dataset is of utmost importance for an accurate measurement of the corresponding variables.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, analysis of PCr recovery kinetics has been extensively used in order to investigate in vivo skeletal muscle mitochondrial oxidative capacity [41], [42]. Previous animal studies reported PCr recovery times typically ranging from ∼50 sec to ∼160 sec according to the end-of-exercise pH values [31], [41], [43]. From a methodological point of view, it should be pointed out that PCr recovery is usually fitted with a monoexponential function so that the temporal resolution of the raw dataset is of utmost importance for an accurate measurement of the corresponding variables.…”
Section: Discussionmentioning
confidence: 99%
“…With repetition time T R  = 6 seconds, this resulted in an effective exercise frequency of 0.3 Hz. To minimize habituation effects28 and standardize exercise conditions, an equivalent preparatory exercise bout was executed 40 min before acquiring MRS data during exercise. The exercise bouts for acquiring data in GM and in SOL were separated by 28 minutes of rest on average (minimum was 20 min), to ensure that PCr, Pi and pH values were fully recovered to basal levels at the beginning of the second bout.…”
Section: Methodsmentioning
confidence: 99%
“…Контраст BOLD (blood oxygen level dependent -зависимый уровень кислорода крови) [132], обладающий способностью обнаруживать акти-вацию мозга, позволяет определять оксигенацию ка-пиллярной и венозной крови в скелетных мышцах и полуколичественно оценивать насыщение крови кислородом [138,139]. В отличие от большинства слу-чаев применения контраста BOLD в исследованиях головного мозга, результат анализа скелетных мышц может быть отрицательным при глубокой кислородной десатурации (падение степени насыщения крови кис-лородом) и положительным, когда выделение тканями кислорода уменьшается [140][141][142][143][144]. Общий и капил-лярный объемы крови влияют на сигнал от контраста BOLD, что осложняет интерпретацию результатов [145].…”
Section: лекции и обзорыunclassified